2022
DOI: 10.3389/fmed.2021.803119
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cyclic Guanosine Monophosphate Is a Promising Biomarker of Clinically Significant Portal Hypertension in Patients With Liver Cirrhosis

Abstract: Introduction: Despite intensive research, reliable blood-derived parameters to detect clinically significant portal hypertension (CSPH) in patients with cirrhosis are lacking. As altered homeostasis of cyclic guanosine monophosphate (cGMP), the central mediator of vasodilatation, is an essential factor in the pathogenesis of portal hypertension, the aim of our study was to evaluate plasma cGMP as potential biomarker of cirrhotic portal hypertension.Methods: Plasma cGMP was analyzed in cirrhotic patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…NILDA are best calibrated for chronic viral hepatitis and ALD etiologies but tend to overestimate CSPH risk in patients with obesity and NAFLD. [23] Promising, but small and nonexternally validated, studies have reported good correlation of contrast-enhanced ultrasoundderived, [73] MRI, [74] and serum biomarkers [75][76][77][78] with HVPG. However, as reviewed in the AASLD NILDA Guideline, correlations between blood-based NILDA and CSPH remains inferior to those with imagingbased NILDA.…”
Section: Do Not Use Deep Sedation (Avoid Fentanyl and Propofolmentioning
confidence: 99%
“…NILDA are best calibrated for chronic viral hepatitis and ALD etiologies but tend to overestimate CSPH risk in patients with obesity and NAFLD. [23] Promising, but small and nonexternally validated, studies have reported good correlation of contrast-enhanced ultrasoundderived, [73] MRI, [74] and serum biomarkers [75][76][77][78] with HVPG. However, as reviewed in the AASLD NILDA Guideline, correlations between blood-based NILDA and CSPH remains inferior to those with imagingbased NILDA.…”
Section: Do Not Use Deep Sedation (Avoid Fentanyl and Propofolmentioning
confidence: 99%